SYNTHESIS AND OPTIMIZATION OF FLY ASH-GRAFTED-POLY(VINYL ALCOHOL/ACRYLIC ACID-CO-METHYL METHACRYLATE) COMPOSITE HYDROGEL AS ANTI-BIOFOULING COATING - MAT GHANI, SITI MUSLIHA (2021)
The working mechanism of hydrogel that uses a water barrier in preventing settlement of biofoulants makes it preferable as compared to the biocide coating. However, the low mechanical strength of hydrogel has limited its application in a harsh environment. Hence, this study was focused on developing fly ash-grafted-poly (vinyl alcohol/acrylic acid-co-methyl methacrylate) (FA-g-P(VA/AAc-co-MMA)) composite hydrogel as an anti-biofouling coating. The low intensity of Fourier Transform Infra-Red (FTIR) spectra’ peaks and morphological changes of microsphere into aqueous phase after integration of the FA confirmed its interaction with the hydrogel.